Insect bite of the lip with secondary impetiginization: a case report - Debré Timothé; El Mansouf Loubna; Meyaz Laila; Moussaceb Saida; Alantar Alp (EDP Sciences, 2021)
Introduction: Impetiginization is defined as a surinfection of Staphylococcus aureus on a preexistent dermatosis: Observation: A 19-year-old patient in good general health was admitted to general emergency and then hospitalized in internal medicine for an abscess of the labial commissure. The anamnesis revealed a 24 hours old insect bite. An abscess of the labial commissure of 20 mm in diameter with a necrotic surroundings and associated induration was observed. After 3 days of antibiotic i.v (amoxicillin + clavulanic acid), the patient went home. By 14 days, healing was complete. Bacteriological examination detected numerous staphylococcus aureus (SA) that were sensitive to meticillin. Discussion: SA by their pathogenicity are responsible for many infections, potentially serious. For several decades, mainly in hospitals, SA have acquired resistance to penicillins A and G. Infections considered as banal could evolve into very serious necrotic infections. Conclusion: This case is unusual because of its localization and its quick evolution on a young adult. It underlines the importance of early bacteriological sampling before the introduction of probabilistic antibiotherapy in order to anticipate extremely serious necrotic infections that may lead to aesthetic and functional sequelae.